Job Stress Among Unskilled Workers in Plantation Divisions at Sime Darby Plantation Sdn. Bhd. - Kamalita, Kamarudin (2011)
This study examined and overview of the causes and consequences of job stress, and of various coping mechanisms among a random sample of 108 of workers at the plantation division of Sime Darby Plantation Sdn Bhd. The descriptive analysis was used to provide information and to determine the amount of variance in job stress levels. A critical examination of literature provides a conceptual framework for understanding the causes of job stress. The research method used for this study relied exclusively on journals, articles from magazines and newspapers, and other applied internet. Research questions were asked; 1. What demographic characteristic predict differences in level of job stress among unskilled workers? 2. What is the level and causes of job stress among unskilled workers? 3. What are worker’s actions and organizational’s effort to prevent the job stress? Research results were not surprising. Participants perceived job stress related to latest development made by organization and lack of support. This research, with support from substantial of evidence, employer and employees should share responsibility for identifying early signs of stress and developing effective coping mechanisms. Such cooperation can assist in preventing a clearly urgent problem.